Alpheid shrimps of the genera Athanas Leach, 1814, Athanopsis Coutière, 1897 and Pseudathanas Bruce, 1983 of the coasts of the Arabian Peninsula (Malacostraca: Decapoda: Caridea) - Anker, Arthur (Zootaxa, 2023)
Several species of alpheid shrimps belonging the genera Athanas Leach, 1814, Athanopsis Coutière, 1897 and Pseudathanas Bruce, 1983 (Decapoda: Caridea) are reported based on material collected on the Red Sea coast of Saudi Arabia and in Oman. Athanas claereboudti sp. nov. is described based on specimens from Masirah Island and Bandar Khayran east of Muscat, Oman, whereas A. iranicus Anker, Naderloo & Marin, 2010, A. minikoensis Coutière, 1903, A. parvus De Man, 1910, and a species tentatively identified as A. cf. dentirostris Anker, Jeng & Chan, 2001, are reported from various Omani localities. In the genus Athanopsis, four species are reported, including one species new to science: A. brevirostris Banner & Banner, 1981 from Saudi Arabia, A. dawa sp. nov. and A. rubricinctuta Berggren, 1991 from Masirah Island, Oman, and A. tarahomii Marin, Sheibani & Sari, 2014 from Saudi Arabia. The records of A. rubricinctuta and A. tarahomii represent second findings and significant extensions of their previously known ranges for these species. An important error in the description and illustration of the colour pattern of A. tarahomii is corrected, whereas the colour pattern of A. brevirostris is compared again with that of A. saurus Anker, 2011; the latter species is newly recorded from New Caledonia. The taxonomic identity of A. platyrhynchus Coutière, 1897, the type species of the genus from Djibouti, remains somewhat problematic. Finally, the monotypic genus Alberta Kazmi & Kazmi, 2010 established for Alberta banneri Kazmi & Kazmi, 2010 is placed in the synonymy of Pseudathanas Bruce, 1983 and Pseudathanas banneri (Kazmi & Kazmi, 2010) comb. nov. is reported from Muscat, Oman, for the first time since its original description. The generic diagnoses of Athanas, Athanopsis and Pseudathanas are emended to accommodate new or transferred species. All species reported are illustrated in colour.